Comparison between Bipolar Hemiarthroplasty and Total Hip Arthroplasty for Unstable Intertrochanteric Fractures in Elderly Osteoporotic Patients - Fan, Lihong (Public Library of Science, 2012)
The present study was conducted to compare bipolar hemiarthroplasty (BA) with total hip arthroplasty (THA) in treatment of unstable intertrochanteric fractures in elderly osteoporotic patients. The THA group included 14 males and 26 females with a mean age of 73.4 years, and the BA group included 27 males and 45 females with a mean age of 76.5 years. Significant difference existed between the two groups in operation time, blood loss, transfusion volume and cost of hospitalization, while no remarkable difference was identified in hospitalization period, general complications, joint function, pain, rate of revision and mortality. No dislocation was observed in BA group while 3 occurred in THA group. The results indicated that for unstable intertrochanteric fractures in elderly osteoporotic patients, BA seems to be a better or more reasonable choice compared with THA for the reason of less blood loss, shorter operation time, lower cost and no dislocation.